(untitled) (Research, Society and Development, 2021)
Endodontic treatment is based on the chemical and mechanical preparation of the root canals, aiming at the removal of microorganisms and preventing reinfection. However, this technique has some limitations and an alternative supporting therapy called Photodynamic Therapy (PDT) has been installed. A physical, chemical and biological procedure that occurs through a reaction between photosensitizers, light, laser and irrigating substances, causing a cytotoxic effect that generates the oxidative reaction, causing cell death through oxidation. Within this context, the objective of this article is to clarify the benefits of PDT in disinfecting the root canal system, in addition to demonstrating its effects and form of use that can assist in the success of endodontic treatment. The methodology used consisted of carrying out a narrative review of the literature, being researched in scientific databases, such as: Scielo, Bvsalud, Redalyc and Sciencedirect. In this way, Photodynamic Therapy acts as an adjunct to endodontic treatment after chemical and mechanical disinfection, minimizing the maximum number of microorganisms persisting in the root canals, without causing damage. It is concluded that PDT is a great alternative to be used together with the conventional technique, even without a specific protocol it can be used, helping with the quality of endodontic treatment.